Relationship between academic goals and prosocial behaviour in social work university students - Suriá Martínez, Raquel; Villegas Castrillo, Esther (Cuadernos de Trabajo Social, 2022)
This study analysed prosocial behaviour and academic goals in a group of Social Work university students. It also identified whether certain combinations of different factors of prosocial behaviour generated different profiles of prosociality. Finally, a verification was performed as to whether any statistically significant differences existed between the groups differentiated according to their academic goals (learning, achievement and social reinforcement). The Prosocial Behaviour Scale (1993), and the Academic Goal Trends Questionnaire (AGTQ, 1991), were administered to a sample of 328 Social Work university students. Their ages ranged from 18 to 30 years (M = 22.56; DT = 4.89). The cluster analysis identified three profiles of prosocial behaviour: a high prosociality profile, a profile of low prosocial behaviour, and a group with a predominance of empathy and trust. The results revealed statistically significant differences between the profiles obtained based on the academic goals they pursued. This finding suggests the need to study prosocial behaviour more in-depth and to design programmes that further strengthen Social Work students’ learning goals.